MANAJEMEN PEMBIAYAAN OPERASIONAL BOARDING SCHOOL PUTRA DARUL HIKAM DAGO GIRI BANDUNG - Acep Husni Mubarok; Iwan Sopwandin; Ara Hidayat (STAI Ma'had Aly Al-Hikam Malang, 2021)
This paper aims to reveal the management of education financing at the Putra Darul Hikam Dago Giri boarding school Bandung. This study uses a qualitative method with the type of field research. The results showed that the education financing management at the Putra Darul Hikam Dago Giri boarding school Bandung, includes: Planning based on the evaluation of the previous year's budget, which was carried out by the Treasurer, Head of Bureau II and Head of Boarding school approved by the college director. Sources of funding are obtained from guardians of students, boarding, donors and foundations. Financing management includes entry and exit costs which include personnel, non-personnel and investment costs. Operational budget supervision is carried out by the Head of Bureau II and the Director of Darul Hikam College. Financial reports are carried out by two parties, namely by the foundation through the Darul Hikam college and by the chairman of the Boarding which is called the Balanced Scorecard (BSC) system.